2021
DOI: 10.1049/gtd2.12151
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated design of delay‐dependent wide‐area damping controllers considering multiple time delays

Abstract: This paper investigates coordinated design of multiple wide-area damping controllers (WADCs) for damping multiple inter-area oscillations considering communication delays in multiple control loop. Two approaches have been investigated: the sequential approach which uses the stability criteria for single delay and design the WADC independently, and the coordinated approach which employs a less conservative and fast Lyapunov stability criterion for linear system with multiple delays to calculate delay margins si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…STATCOM is a compensating device [ 22 ] which will inject or absorb the reactive power according to the system's operating condition but will not dampen out the inter-area mode of oscillations occurring due to physical disturbance. Therefore, a supplementary damping controller is designed to dampen the oscillations [ 23 , 24 ]. The structure of the damping controller consists of three block namely the gain block, washout block and phase compensation block.…”
Section: Design Of Statcom Based Lead Lag Damping Controllermentioning
confidence: 99%
“…STATCOM is a compensating device [ 22 ] which will inject or absorb the reactive power according to the system's operating condition but will not dampen out the inter-area mode of oscillations occurring due to physical disturbance. Therefore, a supplementary damping controller is designed to dampen the oscillations [ 23 , 24 ]. The structure of the damping controller consists of three block namely the gain block, washout block and phase compensation block.…”
Section: Design Of Statcom Based Lead Lag Damping Controllermentioning
confidence: 99%
“…Simulation results demonstrated that the inter-area oscillations are significantly damped while controlling the reactive power output of the wind turbines. Authors of reference [26] coordinated multiple WADCs for damping various inter-area oscillations, while incurring some communication time delays in controller channels. A less conservative and fast Lyapunov stability function is used to determine the time delay margins and coordinate the design of WADCs.…”
Section: Introductionmentioning
confidence: 99%